(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This study is driven by the fact that teachers often employ monotonous teaching strategies; when there is no variation in the methods used, learning becomes dull and lowers student learning outcomes. Instead of engaging in learning, students typically engage in other activities. The purpose of this study is to determine whether the Index Card Match method at SMA N 1 Hiliran Gumanti improves student learning results. This study examines the impact of the index card match method on student learning outcomes using quantitative methods and a quasi-experimental design. Purposive sampling was used to choose 51 pupils from the population of 79 students. SPSS 26 was used to analyse the data. The study’s findings demonstrate the value of the Index Card Match approach in improving class X (Phase E) students at SMA Negeri 1 Hiliran Gumanti’s learning objectives. Evaluate efficacy with the N-Gain score. According to the research findings, the Index Card Match Method is excellent at enhancing student learning outcomes because, in the paired sample t test, t count = 8.018 and significance = 0.001 indicate that H0 is rejected. The results of the Independent Sample t test showed that H0 was rejected when t count = 2.515 > t table = 2.00958 and significance = 0.015 < 0.05. When the N-Gain score was tested, the medium category’s average N-Gain was found to be 0.4373, within the interval 0.2 < d < 0.8. The study concludes that for Islamic Religious Education class X Phase E SMA N 1 Hiliran Gumanti, the Index Card Match approach improves learning results more than the lecture method.